Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1002/macp.1986.021870812
|View full text |Cite
|
Sign up to set email alerts
|

Composition‐properties relationships in propene‐ethene random copolymers obtained with high‐yield Ziegler‐Natta supported catalysts

Abstract: The crystallization and thermal behaviour of crystallizable random propene/ethene copolymers (P-co-E) was systematically investigated. Index of crystallinity and, index of y-form, enthalpy and entropy of fusion, equilibrium melting temperature, spherulite growth rate, and overall kinetic rate constant were determined and correlated with the overall ethene content and with the concentration of specific chemical defects as determined by "C NMR analysis (PEP, EPP, EPE triads). The samples of the copolymers, obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…24, along with our fitting equations to these data. Figures 24a and 24b show that 7^, A/7 f°, and o e all decrease rapidly with increasing m [70], consistent with inclusion of an appreciable fraction of ethylenic repeat units into iPP crystallites. These data can be fitted reasonably well byEqs.…”
Section: Isotactic Poly(propyiene-co-1-ethylene)supporting
confidence: 67%
See 1 more Smart Citation
“…24, along with our fitting equations to these data. Figures 24a and 24b show that 7^, A/7 f°, and o e all decrease rapidly with increasing m [70], consistent with inclusion of an appreciable fraction of ethylenic repeat units into iPP crystallites. These data can be fitted reasonably well byEqs.…”
Section: Isotactic Poly(propyiene-co-1-ethylene)supporting
confidence: 67%
“…Avella et al [70] studied the crystallization of propylene-rich random copolymers of propylene with ethylene, provided by Himont, for which the resins were synthesized with a third-generation, high-yield supported catalyst system (a superactive catalyst). They found trends similar to those they had found earlier [63][64][65][66] for copolymers of propylene and 1-butene.…”
Section: Isotactic Poly(propyiene-co-1-ethylene)mentioning
confidence: 99%
“…In the reheating curves (Fig. 3(c) and (d)) for each fraction besides the main melting peak, there exists a weak shoulder peak at low temperature side, which, unambiguously, results from the melting of small amount of g-form crystals [19,24,29,32], as mentioned above. It should be pointed out that the fractions eluted at room temperature (25 8C), PPE1-25 and PPE2-25, exhibit elastomer characteristics.…”
Section: Resultsmentioning
confidence: 84%
“…It should be pointed out that the introduction of ethylene unit in iPP backbone can modify crystallization behavior of iPP, not only crystal morphology but also crystal structure. Early studies indicated that g-form crystals could be formed by short propylene sequences, while the long sequences crystallizaed into a-form crystals [19,24,[26][27][28][29][30][31][32][33]. Thus, the PPE may exhibit complicated crystallization behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation